Antifungal performance of essential oils in breadmaking by in situ, in vitro and active packaging evaluation – a review (Research, Society and Development, 2022)
Due to antifungal properties, the application of essential oils in bread has attracted commercial interest due to its highly perishable. Their limited shelf life is due to their high water activity and is dependent on good manufacturing practices and proper storage and distribution methods. The main spoilage microorganisms in bread are molds. Therefore, the present study aimed to provide an integrative review of scientific literature related to recent studies on the application of essential oils to limit or prevent the development of spoilage fungi in breadmaking. The approach includes the use of essential oils as an additive in the formulation of bread through addition in the dough, as surface protection or in active packaging. Essential oils are composed of bioactive substances with antifungal properties that are suitable for the preservation of bread. High volatility, high costs, and strong odors are characteristics that restrict their applicability. Therefore, it is important to evaluate the dosage, forms of application, different mechanisms of antimicrobial action, and the effects of their individual or combined use with other preservation technologies. In this way, essential oils there may be inhibitory to spoilage microorganisms while maintaining adequate technological and sensorial characteristics in breadmaking.